Reformasi Birokrasi Pelayanan Publik dalam Meningkatkan Kualitas Pelayanan Kesehatan di RSUD Dr. Moewardi (Pencanangan Pembangunan Zona Integritas WBK & WBBM) - Estining Nur Kartika; Sudarmo Sudarmo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
Bureaucratic reform has the meaning of major changes in Indonesian governance to create good government agencies in providing services to the community. Various government agencies are competing to commit to bureaucratic reform, one of which is regional hospitals which are bureaucratic institutions engaged in health services. Hospitals that work in the medical or health sector bear a double burden because they have to guarantee the quality of health services and also organize their bureaucracy. Therefore, efforts to reform the public service bureaucracy in hospitals are interesting to be studied further. Through qualitative research, this article analyzes the process of reforming the public service bureaucracy at RSUD Dr. Moewardi in improving the quality of health services. Data were obtained from interviews, observations, and document analysis on the direction of changes in bureaucratic reform to improve the quality of public services which were then analyzed using the PDCA cycle (plan, do, check, act). Through this analysis, it can describe the efforts of RSUD Dr. Moewardi in controlling the commitment to bureaucratic reform to improve the quality of public services.